Produksi dan Usahatani Padi Varietas Unggul Baru di Lahan Rawa Lebak Kabupaten Banyuasin Sumatera Selatan - Suparwoto Guwat; Waluyo Waluyo; Priatna Priatna (Politeknik Negeri Lampung., 2017)
One component of technology that has a real role in improving the production and quality of agricultural commodities is superior varieties, such as adaptive varieties and high yield potential in swampy land, especially rice. The purpose of the assessment is to obtain varieties that have high production, good plant growth and income information on rice farming in swampy land. The study was conducted in Sako Village, Banyuasin Regency, South Sumatera Province starting in the dry season of 2016. The varieties studied were 4 varieties: Inpari 15, Inpari 22, Inpari 30 and Inpara 4. The assessment was prepared based on a randomized block design (RAK). The observed variables were: plant height, number of productive tillers, panicle length, number of grains per panicle, percentage of grain of fill per panicle, and yield of dry grain harvest. Data analysis used variance analysis and continued with Duncan test at 5% level. The results showed that the production of Inpari 15, Inpari 22, Inpari 30 and Inpara 4 was 4.9 tons gkp / ha, 6.8 tons gkp / ha, 6.1 tons gkp / ha, 7.0 tons gkp / ha. Financially, the use of Inpari 22, Inpari 30 and Inpara 4 superior varieties is feasible to develop and benefit with the BC ratio > 1.0.